Karakteristik Hidrologi dan Pengelolaannya dengan Model Hidrologi Soil and Water Assessment Tool Sub DAS Cisadane Hulu - Widya Ulfah Utami; Enni Dwi Wahjunie; Suria Darma Tarigan (Jurnal Ilmu Pertanian Indonesia, 2020)
One of the priority watersheds to be managed in Indonesia is the Cisadane watershed due to the high degradation problems. The Cisadene watershed degradation could be indicated by a high river flow during rainy season, low baseflow in dry season, and high erosion and sedimentation. One of the main problems in the Cisadane watershed is a huge landcover changes in the Cisadane Hulu watershed that causes a decrease in water absorption region and a surface runoff. The study aimed to analyze landcover changes in the Cisadane Hulu Watershed during 2013-2018 and analyze the watershed conditions based on their hydrological characteristics. Analysis of landcover changes patterns was carried out by processing spatial data using GIS software. Analysis for hydrological characteristics was conducted by using SWAT modelling (Soil and Water Assessment Tool). The results showed that there were land cover changes during 2013-2018. The most significant landcover changes in the Cisadane Hulu watershed was residential area (455.95 ha). The result simulation scenario of the model SWAT showed scenario 2 was the best scenario for the management of the Cisadane Hulu watershed. The application of Soil and Water Conservation can decrease surface runoff by 32.1% and increase lateral flow by 8.89%. Therefore, it is expected that the results of this SWAT model simulation will be taken into consideration by the local government for the optimal management of the Cisadane Hulu watershed. Keywords: Cisadane watershed, land cover change, SWAT modelling